Epidemiological Characteristics and Trends in the Incidence of Newly Diagnosed Pulmonary Tuberculosis in China from 2016 to 2022 - Caihong Xu; Yaxin Wen; Dongmei Hu; Yuhong Li; Yanlin Zhao (Zoonoses)
This study was aimed at exploring pulmonary tuberculosis (PTB) epidemiological characteristics and trends in China from 2016 to 2022, to provide evidence for optimizing strategies and measures for tuberculosis prevention and control. Data on PTB in China reported from 2016 to 2022 were obtained from the Chinese Disease Prevention and Control Information System. Descriptive epidemiological methods were used to analyze the population distribution, and temporal and spatial distribution (also known as the three-dimensional distribution in epidemiology). The chi-square test was used for comparisons between groups. Joinpoint regression was used to analyze the temporal trends in PTB notification rates, and ArcGIS 10.3 software was used to visualize the results. In total, 5,141,468 cases of PTB were reported in China from 2016 to 2022, among which 39.89% were bacteriologically positive. Joinpoint regression analysis indicated that the PTB notification rate showed an overall downward trend from 2016 to 2022, with 2018 as the inflection point. The annual percentage change (APC) was −0.72% (95% CI: −4.78% to 2.96%, P <0.001) from 2016 to 2018, and −9.26% (95% CI: −11.76% to −8.08%, P <0.001) from 2018 to 2022; the overall average annual percentage change (AAPC) was −6.50% (95% CI: −7.56% to −5.51%, P <0.001). The population distribution indicated that the male to female ratio was 2.19:1.00. Individuals older than 65 years accounted for 25.93%. Occupation distribution analysis indicated that farmers accounted for more than 60%. The PTB notification rate showed the following spatial distribution: western region > central region > eastern region. Guangdong province had the highest number of reported PTB cases. From 2016 to 2022, the PTB notification rate showed an overall downward trend in China. Men, older people, and farmers were the majority groups. The western region and Guangdong province were hotspots that must be addressed. In the future, the Tuberculosis prevention and control strategies should be optimized according to epidemiological characteristics.